Close toleranced sheet and strip of aluminium-copper-magnesium-silicon-manganese alloy (Solution treated and aged at room temperature) (Cu 4.4, Mg 0.5, Si 0.8, Mn 0.8) - 8096 British Standards Institution
PSZJBL